2022
DOI: 10.3390/antiox11010127
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Insight into Screening for Antioxidant Peptides from Hazelnut Protein: Based on the Properties of Amino Acid Residues

Abstract: This study used the properties of amino acid residues to screen antioxidant peptides from hazelnut protein. It was confirmed that the type and position of amino acid residues, grand average of hydropathy, and molecular weight of a peptide could be comprehensively applied to obtain desirable antioxidants after analyzing the information of synthesized dipeptides and BIOPEP database. As a result, six peptides, FSEY, QIESW, SEGFEW, IDLGTTY, GEGFFEM, and NLNQCQRYM were identified from hazelnut protein hydrolysates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…This indicated that YPVEPF and YPVEP might have the potential to improve neuron inflammation against oxidant stress. Many studies showed that the presence of a Tyr residue with electron/hydrogen-donating ability was the driving force for peptides to scavenge radicals. , Therefore, the calculation results further highlighted the fact that the Tyr residue should act as a bioactive site, and QM is a useful assay to explore the structure–activity relationship. As previously described, the YXXY pattern in peptides could be the vital potential of the BZD site affinity, as the distance between the centers of the two tyrosine aromatic rings is similar to that between the centers of the aromatic rings in nitrazepam .…”
Section: Resultsmentioning
confidence: 95%
“…This indicated that YPVEPF and YPVEP might have the potential to improve neuron inflammation against oxidant stress. Many studies showed that the presence of a Tyr residue with electron/hydrogen-donating ability was the driving force for peptides to scavenge radicals. , Therefore, the calculation results further highlighted the fact that the Tyr residue should act as a bioactive site, and QM is a useful assay to explore the structure–activity relationship. As previously described, the YXXY pattern in peptides could be the vital potential of the BZD site affinity, as the distance between the centers of the two tyrosine aromatic rings is similar to that between the centers of the aromatic rings in nitrazepam .…”
Section: Resultsmentioning
confidence: 95%
“…Hydrophobic amino acid residues, such as His, Trp, Phe, Pro, Gly, Lys, Ile and Val, are attributed to strong radical scavenging activity in oxidative reactions, especially for enzyme-catalysed reactions, due to the imidazole ring from histidine as a vital proton donor [ 134 ]. In addition, the indole and pyrrolidine rings in Trp and Pro and Tyr, Cys and Met can also serve as hydrogen donors through their hydroxyl and thiol groups, thus acting as scavengers of hydroxyl and other free radicals [ 134 , 135 ]. Peptides obtained by simulated gastrointestinal digestion of hemp seeds, WVYY and PSLPA, showed the best antioxidant and antihypertensive properties, pointing to the presence of three aromatic amino acids, Trp, Tyr and Pro, in acquiring the pronounced antioxidative peptide properties [ 136 ].…”
Section: Food-derived Bioactive Peptides With Antioxidant Activitymentioning
confidence: 99%
“…OSM–H considerably increases the AV after 7 days of storage but without surpassing NC. Shi et al [ 67 ] mention that Tyr, Trp, Met and Cys amino acids confer excellent antioxidant capacities to hazelnut protein peptides, acting as important hydrogen donors for free radicals. Among these amino acid residues, they found that Tyr-containing peptides exert a significant antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%